A noble-metal-free photocatalytic hydrogen production system based on cobalt(iii) complex and eosin Y-sensitized TiO2. Issue 3 (5th December 2014) - Yin, Mingcai; Ma, Shuang; Wu, Chaojun; Fan, Yaoting
Abstract : With CoL2 as cocatalyst and eosin Y as sensitizer, the noble-metal-free heterogeneous CoL2/TiO2 system shows much efficient and more stable hydrogen evolution activity than that of the homogeneous system under visible light irradiation. Abstract : Although dye-sensitized TiO2 for photocatalytic H2 production have been investigated for more than 20 years, research on using low-cost transition metal complexes as catalysts for proton reduction on TiO2 is still relatively rare. In this paper, three cobalt complexes (CoL1–CoL3) were prepared and used as hydrogen evolution catalysts, and a noble-metal-free H2 -evolving system was fabricated by using an organic dye, eosin Y (EY), as photosensitizer and triethylamine (TEA) as sacrificial agent. Under visible light irradiation, a turnover number of 90 (based on CoL2) was obtained for 2 wt% CoL2/TiO2 within 6 h in aqueous solution under the optimal conditions of 4 μmol EY, 5% TEA (v/v) and pH 11. In addition, much higher hydrogen production efficiency and stability were achieved for the heterogeneous system, in comparison with the homogeneous one.